Virtual testing of existing semi-rigid rockfall protection barriers. (15th February 2015) - de Miranda, S.; Gentilini, C.; Gottardi, G.; Govoni, L.; Mentani, A.; Ubertini, F.
Highlights: The performance of semi-rigid rockfall protection barriers is considered at failure, at service and maximum energy level through a FE study. The results of the numerical analyses allow to assign a capacity value to the selected type of semi-rigid rockfall protection barriers. Numerical analyses enabled to study the failure mechanisms of selected type of semi-rigid rockfall protection barriers. Results of the numerical analyses can be used in the management of existing semi-rigid barriers. Results of the numerical analyses can be implemented in rockfall hazard assessment tools. Abstract: Semi-rigid rockfall protection barriers are steel structures constituted by a principal interception structure made of cables mounted on structural steel posts fully restrained to the ground. Traditionally, they are assigned a low capacity value which ranges from few to less than 300 kJ. Over the last decades, semi-rigid rockfall protection barriers have been installed along areas interested by rockfall events, often in conditions of extreme urgency, without a specific structural design. As a result, they are found in a variety of subtypes, most of them lacking the essential structural information, such as the energy absorption capacity, crucial for a reliable application of procedures for quantitative risk assessment. To fill this gap, and considered the lack of experimental data on semi-rigid barriers, in the present study a numerical investigation of the most common barrier subtypes is developed. In the absence of standards for this kind of barriers, the barriers are virtually tested in conditions inspired by the essential prescriptions included in the European Guideline for flexible barriers (ETAG 27). Results allow to: (i) investigate the performance of the barriers in service condition; (ii) provide an estimate of the barrier capacity and (iii) explore the barrier failure mode.